If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5b + 7 = 1 + -8b Reorder the terms: 7 + -5b = 1 + -8b Solving 7 + -5b = 1 + -8b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '8b' to each side of the equation. 7 + -5b + 8b = 1 + -8b + 8b Combine like terms: -5b + 8b = 3b 7 + 3b = 1 + -8b + 8b Combine like terms: -8b + 8b = 0 7 + 3b = 1 + 0 7 + 3b = 1 Add '-7' to each side of the equation. 7 + -7 + 3b = 1 + -7 Combine like terms: 7 + -7 = 0 0 + 3b = 1 + -7 3b = 1 + -7 Combine like terms: 1 + -7 = -6 3b = -6 Divide each side by '3'. b = -2 Simplifying b = -2
| 2/3(9-m)=2m | | 6/11x7/11 | | 205=-5(1-7x) | | 9(y-2)/4=-4y | | 2x-6-4=-7 | | x=11x | | 7w+1-5w+3=5+2w-1 | | -4(6+7x)=-248 | | 8x+4x+3+9=3x+3+8x | | (B+6)+(B-6)=2B | | lnx-ln(x^2)=5 | | 8(4x+4)-6x=-272 | | -3(6x-7)=147 | | 2u-10=20 | | -5(-2x+5)=85 | | -5=5+5n | | -4w=-16 | | .5(x+9)-2=7 | | -5(-2+5)=85 | | 5(-2x+6)=3(4x-10) | | d-54=1.83 | | -12x-16y=3 | | 4a-a=3 | | 7(5-6k)=-7(7+7k) | | 13+6m=3m+1 | | 4w+3-8w+5=-3-4w+11 | | 7(6-4x)=266 | | 6(1-14)=1(1-3x) | | 1-3x=1-2 | | 3x-74=10 | | p+7=4p | | -128=-16t^2-16t |